Effect of delaying winter pruning of Bobal and Tempranillo grapevines on vine performance, grape and wine composition. (15th November 2020) - Buesa, I.; Yeves, A.; Sanz, F.; Chirivella, C.; Intrigliolo, D.S.
Abstract: Background and Aims: Climate change is advancing grapevine phenology, decoupling berry technological and phenolic maturity. The aim of this study was to assess the usefulness of late winter pruning for delaying grape ripening. Methods and Results: In two Bobal and Tempranillo vineyards located in eastern Spain, vines pruned at dormancy were compared with a delayed winter pruning (late pruning) carried out just before the basal buds burst (BBCH 05). In both cultivars, late pruning delayed grape ripening, resulting in grapes with higher anthocyanin concentration for similar TSS at harvest. In general, the resulting wines had a higher colour intensity and lower hue angle. These effects were more noticeable in Tempranillo, an earlier ripening cultivar, than in Bobal. Despite late pruning improving vine water status, the yield was steadily reduced by 10%. Conclusions: Late pruning is a useful strategy for delaying grape ripening, thus adapting grapevine production to climate change. The small detrimental effects on yield and compression of pruning dates within a few days may limit the application of this practice. Significance of the Study: Delaying winter pruning can be used to improve grape and wine composition when facing changes in the meteorological conditions experienced during berry ripening.